Research on the Ideological and Political Construction of the Course "Internal Control and Risk Management" from the Perspective of New Quality Productivity - Zhong, Yangmei; Nie, Xiaopeng (International Journal of Social Sciences and Public Administration, 2025)
This article focuses on the empowerment of new quality productivity in the ideological and political construction of the course "Internal Control and Risk Management" in universities. It deeply analyzes the necessity and feasibility of integrating ideological and political elements into the course, explores the internal logic of empowering the ideological and political construction of the course "Internal Control and Risk Management" with new quality productivity from the aspects of training objectives, concept coordination, and content correlation, and proposes specific construction paths such as exploring the connotation of ideological and political education, innovative means and methods, building a high-quality teacher team, and constructing a perfect course ideological and political evaluation system, in order to cultivate internal control and risk management professionals who not only have solid professional knowledge but also good moral qualities and social responsibility, adapt to the development needs of new quality productivity, and promote the innovative development of ideological and political education in university courses.